Art collecting of Cuzco painting school in Lima during the eighteenth century - Holguera Cabrera, Antonio (2018)
In the field of art history, documentary sources are valuable for understanding the cultural interrelations of social groups, as they allow us to trace the origin, criteria and evolution of collecting, closely linked to the development of historical and artistic trends in flourishing cultural centers. The article draws an assessment of the holdings of Cuzco painting school in Lima’s homes during the eighteenth century and analyses the taste of the capital’s elite based on their artistic collections.